Perancangan Sistem Parkir Otomatis Berbasis Plc Mitsubishi Fx3u Ditaman Rekreasi - Sadi, Sumardi; Susanto, Andri; Riansyah, Bima (Jurnal Teknik Elektro, 2025)
The growth in the number of vehicles in urban areas and limited parking spaces available further exacerbate the problem of finding empty parking spaces. Inefficient parking management can result in congestion, waste of time, and increased security risks for parked vehicles. To overcome this problem, this research focuses on the design and implementation of an automatic parking system based on Mitsubishi's Programmable Logic Controller (PLC) which is designed to increase parking efficiency, vehicle safety and user comfort.The automatic parking system developed utilizes proximity sensors to detect and monitor the availability of parking spaces in real-time. This sensor detects the presence of vehicles in each parking slot and sends status information to the PLC control unit. To providevisual information to users, the system is equipped with two indicator LEDs: a green LED indicating that the parking space is still available, and a yellow LED indicating that the parking area is full. This system design ensures that all components function synergistically to optimize the parking process. The use of Mitsubishi PLC as the main control ensures the stability and reliability of the system in processing sensor data and controlling indicators. With this system, dependence on human labor can be reduced, and the risk of operational errorsthat are common in manual parking systems can be minimized.The results of this research show that this automatic parking system has succeeded in reducing the time needed to find a parking space, increasing the level of vehicle safety with clear status indicators, and providing a more efficient solution compared to conventional parking methods. Implementation of this system not only provides practical benefits for parking managers and vehicle users, but also has the potential to be applied on a wider scale in various urban environments.